Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Global Television Formats in Africa: Localizing Idol - Nkosi Ndlela, Martin (Global Television Formats: Understanding Television Across Borders, 2012)
During the last decade, popular television formats have been replicated across the globe for local or regional consumption as program imports, adaptations, clones or imitations, raising questions on the possible ramiﬁcations of such cultural inﬂows. For Africa the international program ﬂow and the inﬂuence of Western media content has been a contentious issue for decades, underlying the cultural imperialism thesis of the 1970s and 1980s, and the centre– periphery paradigms which conceptualized the series of dependency relationships. In African media research concepts like cultural colonialism, media imperialism, neocolonialism, Americanization, homogenization, have been used to denote the unequal ﬂow and inﬂuence of Western media products in Africa. Within the framework of media globalization some scholars have even propounded a scenario of the emergency of a global culture mediated by the dominant Western media. The central issues in African media discussions have mainly revolved around the ﬂow of ﬁnished media programs and their perceived detriment to local cultures and identities. What is missing in the African research literature is the attention to television formats, a phenomenon described by Keane et al. (2002) as a vehicle for localization, since what is imported is not the content itself, but a recipe for creating a local version. Global reality format shows thus create a new picture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); Ghana (corpus analysé); Nigéria (corpus analysé); Norvège (lieu de production du savoir); _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé